Determination of The Effect of Growth Regulators on Germination Properties of Silage Sorghum - KIZIL AYDEMİR, Serap and DEVLET, Ali (ISPEC Journal of Agricultural Sciences, 2023)
Due to the decrease in the quantity and quality of water resources in the world, drought stress becomes important in plant cultivation and causes changes in the physiological functions of economically important plants. In order to obtain products in an economic sense, the optimum environmental requirements of the plant species or variety grown must be met. In order to increase these environmental demands, the use of plant growth regulators, inspired by the regulating hormones naturally found in the plant itself, is a common method recently. In our study, it was aimed to increase germination and germination factors by using plant growth regulators in silage sorghum. In the research, Nes sorghum variety, which was determined to be compatible with the region in the previous cultivar yield study in the region, and Zeatin and Brassinolides growth regulators were used as materials. Sorghum seeds were placed in each petri dish with filter paper. Germination experiments of seeds were carried out at 20/25°C (day/night) for 10 days. Germinated seeds were counted at the same time each day. When the rootlet reached 2 mm, the seed was considered to be germinated and removed from the petri dish. At the end of the research, the highest germination rate of sorghum seeds for silage was obtained from 1% Zeatin + 1% Brassinolides application with a value of 98.97%. Average values between 2.15 and 1.93 in the period until 50% germination were obtained from the control application with the highest value of 2.15. Average germination index values varied between 36.80 and 28.84, and the highest germination index was obtained from 1% Zeatin + 1% Brassinolides application. At the end of the research, it was determined that hormone applications had positive effects on the germination of silage sorghum seeds.